UJI “KETAHANAN LELAH DAN PENURUNAN GAYA PEGAS “ KATUP KOMPRESI AKIBAT “BEBAN OPERASI” PADA KATUP MOTOR DIESEL OUTPUT RATED 400 kW. - Djaya, Yuhani; Hatuwe, Mohammad Rusdy (Bina Teknika, 2015)
Major role in the valve spring Diesel 4 strokes is able to guarantee the valve open and closed positions without loss of engine compression. Therefore, the spring must be able to maintain the style required by the valve in accordance with the needs of its operations. When the spring force reduction operations over the threshold, then the spring will be malfunctioning. Before this happens, the spring should be replaced or restored. Meanwhile, the replacement with a new one because it failed to cause unplanned downtime. To balance the needs of utilities and prevention of failure (downtime) is required prediction faill replacement, and therefore the rate of decline in the spring force is directly related to the characteristics possessed by every spring, then to determine the rate of decrease in the valve spring force necessary to test fatigue characteristics. To achieve these objectives, characteristics and fatigue testing is done with spring material Goodman line approach. These tests include the identification of test material in the form of a test spring spring material chemical composition and hardness test; namely to determine the tensile strength limit in the diagram Heigh and criteria preset limit or unpreset spring tired. Next proceed to test the rate of decrease in the spring force on the cyclic loading which is the subject of this study, in which the rate of decrease in the spring force test due to cyclic done to reach the threshold spring force on the round number above 107. The test results showed that the decrease in the spring force caused by the spring force on the rate of decline of about 6% cyclic loading is at about 300 hours of operating hours, the next spring force experienced stability.